030 Management of bifurcation disease with a dedicated side-branch device; a single centre experience with the tryton stent. (16th May 2012) - Venugopal, V; Singh, R; Martins, J; Norell, M
Abstract : Background: The optimal strategy for the treatment of bifurcation disease is not yet defined. While trial data suggests that "provisional" side-branch (SB) stenting may be superior to more complex 2-stent approaches, the role of customised devices designed specifically to treat this complex anatomy has not been examined. The TRYTON side-branch stent is one such example. This is a 5 French guide compatible, non-drug eluting, Cobalt Chromium device mounted on a monorail balloon catheter. When deployed into the SB, it is specifically designed to scaffold the ostium. A second stent is mandated in the main branch (MB) and deployed through TRYTON in a culottes fashion, serves to further cover the carina and secure TRYTON. This is followed by final kissing balloon inflation. Methods: All patients undergoing bifurcation stenting using the TRYTON stent were systematically included in a registry. Follow-up data were obtained by case note and angio review and telephone interview. Results: Since November 2008, 79 patients (mean age 63 years, range 36–84) with bifurcation disease and SB vessel diameters of at least 2.5 mm were selected for treatment with TRYTON in our centre. 75% (59/79) of the target lesions were in the left anterior descending/diagonal while 4 were in the left main stem. 60% (47/79) lesions were Medina 1.1.1, while 15% (12/79) had no SB disease. Procedural success was achieved in 94%. In 5 cases from our initial 6 months' experience, TRYTON could not be delivered to the target lesion due to proximal calcification or tortuosity, resulting in stent dislodgement in 4 cases and requiring retrieval of TRYTON in 1. An alternate bifurcation strategy was used and none of the 5 patients suffered clinical sequelae. Subsequent device modification by the manufacturers to improve balloon adherence, trackability and deliverability resulted in a 100% success rate. In the remaining 74 patients TRYTON was deployed successfully and in all but one case, a drug eluting stent was used in the main branch. Additional drug eluting stents were deployed into further diseased segments of the SB in five cases and the MB in 28. Final kissing balloon inflation could be performed in all but one case (99%). Angiographic success in both the main and side branches was 100%. After a median follow-up of 18 months (range 2–40), there have been no instances of unplanned readmission with ischaemia, myocardial infarction or death in any of the 79 patients. In one case in-stent restenosis in the bare-metal MB stent required further treatment with a drug eluting balloon. Conclusion: TRYTON performs predictably and successfully scaffolds the side-branch ostium. The enhanced ability to rewire the side-branch for final kissing balloon inflation when compared with other 2-stent strategies may have contributed to our low observed clinical event rate. The medium term results in this series are encouraging. A randomised trial comparing TRYTON with provisional side-branch stenting is ongoing.